“Tollers Zelle” by Anna Korsun: at intersection of Musical Interpretations - Hnativ, Nataliya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. Exploring the music of Anna Korsun, who at the moment is one of the most famous, titled and most promising young composers in Europe, the author of the article emphasizes that this allows to learn about the latest processes in European academic music. Considering A. Korsun’s Ukrainian origin, this kind of research is especially important for Ukrainian musicology. The small number of publications, the almost complete absence of scientific works about the composer’s creativity in general or about her specific composition determine the novelty of this article, devoted to a detailed analysis of the “Tollers Zelle” for electric guitar and soprano. This is one of the last vocal works of A. Korsun. The main objective of the study is to identify the musical interpretive potential of the vocal piece “Tollers Zelle”. The methodology in the article is based on methods of structural, linguistic and comparative analysis. Results. The vocal piece “Tollers Zelle” was written by A. Korsun as an assignment with the obligatory condition of using the text based on some specific poem. The composer placed the text of the selected poem by E. Toller at the end of the work immediately after music and chose the life and creativity of the poet in general as the basis of the image system of the piece. According to the mind of author of this article, the content palette of the work consists of images of stupor, pain, solitude, disorder of consciousness, that are realized through dissonant verticals, glissando technique, expressive character of performance, transformation of electric guitar sound into a voluminous, rattling, and cold one with elements of playfulness using a glass and a toy musical box, making a voice close to the sound of an electric guitar. Versions of almost all performers of “Tollers Zelle” differ in some more loose aspects (the pitch and rhythm lines are non-fixed precisely, tempo “ad libitum”) and are close in basic elements — manner of playing and singing, dynamics. Conclusions. The vocal piece “Tollers Zelle” can be analyzed in aspects of composer’s, musicological and performer’s interpretation. The composer’s interpretation demonstrates an original solution of the assignment condition, that indicates the non-standard thinking of A. Korsun within her aesthetic principles. Musicological interpretation by author of this article finds the main images and musical technical aspects of the piece “Tollers Zelle”, its inclusion in the A. Korsun’s individual style and also the closeness of almost all performer’s versions of the piece.